Cohesive properties of wheat flour and their effect on the size-based separation process - Siliveru, Kaliramesh (Kansas State University, 2016)
Wheat flour processing involves gradual size reduction and size-based fractionation of milled components. The size-based separation efficiency of wheat flour particles, with minimum bran contamination, is an important flour mill operational parameter. The flour particles often behave as imperfect solids with discontinuous flow and agglomerates during the separation process due to their differences in physical and chemical characteristics. Noticeable loss in throughput has been observed during sieving of soft wheat flour compared to that of hard wheat flour due to differences in inter-particle cohesion. However, there is limited understanding on the factors that influence the inter-particulate forces. Direct and indirect methods were applied to investigate the effects of moisture content, particle size, sifter load, and chemical composition on the cohesion behavior of flours from different wheat classes. Image analysis approach was used to quantify the particle characteristics such as surface lipid content, roughness, and morphology with respect to particle size to better understand the differences between hard and soft wheat flours. Surface lipid content and roughness values showed that the soft wheat flours are more cohesive than hard wheat flours. The morphology values revealed the irregularity in flour particles, irrespective of wheat class and particle size, due to nonuniform fragmentation of endosperm particles. The chemical composition significantly contributes to the differences in cohesion and flowability of wheat flours. Based on the particle parameters, a granular bond number (GBN) model was developed to predict the dynamic flow of wheat flour. In order to further understand the wheat flour flow behavior during size-based separation, a correlation was developed using the discrete element method (DEM). The error of predictions demonstrated that this correlation can be used to estimate the sieving performance and sieve blinding phenomenon of wheat flour. The experimental results from this dissertation work and the numerical model could eventually be instrumental to improve the efficiency of size-based separation of flour from various wheat classes. In addition, the models developed in this study will contribute significantly to understand the inter-particle cohesion as influenced by chemical composition.
Keywords: Wheat flour; Cohesion; Size-based separation; Flow properties; Discrete element method